Transformation and Sustainability: The Canvas Business Model in SMEs in The New Normal - Bayu Ciputra Satrio; Basuki Wibawa; Himawan Hadi Sutisno (PT. Anagata Sembagi Education, 2024)
This study aims to explore how Small and Medium Enterprises (SMEs) in the manufacturing sector adapt to the Canvas Business Model in facing the challenges posed by the COVID-19 pandemic and the New Normal era. Using a qualitative approach, data were collected through in-depth interviews with owners and managers of manufacturing SMEs in various regions. The results show that transformations in customer segments, value propositions, and distribution channels are key to maintaining business sustainability. Significant changes also occurred in customer relationships and revenue streams, where innovation and digitalization played a critical role. Successfully adapted SMEs demonstrated flexibility in cost structures and key partnerships, allowing them to respond quickly to market changes. The study concludes that the adoption of the Canvas Business Model helped manufacturing SMEs not only survive but also thrive amidst the uncertainty caused by the pandemic. The practical implications of this study provide valuable insights for practitioners and policymakers in supporting SME sustainability in the post-pandemic era. Recommendations for further research include further exploration of the long-term impacts of these adaptation strategies.